"I don't just drink water for the sake of it": Understanding the influence of value, reward, self-identity and early life on water drinking behaviour. (July 2022) - Rodger, Amy; Papies, Esther K.
Highlights: Associating water with reward was associated with high, consistent, and subjectively effortless intake. Drinking water out of obligation (i.e., no reward) was associated with low, inconsistent, and effortful intake. Participants with health-conscious self-identities were more likely to associate water with reward. The association between health-consciousness and reward was disrupted when other aspects of self-identity were more prominent. Drinking patterns from early life persisted into later life and were experienced as hard to change. Abstract: The prevalence and negative health outcomes of underhydration call for a better understanding of water drinking motivations to inform interventions. This mixed methods study assessed the motivational processes underlying different patterns of water intake (i.e., high versus low) with a focus on the constructs like value, reward, self-identity and early life drinking habits. We used an initial quantitative survey (N = 400, M age = 24, N female = 293 ), followed by a qualitative survey (N = 101, M age = 33, N female =  75) in the general UK population. The quantitative survey assessed self-reported differences in water drinking behaviour (e.g., amount and frequency) in high and low water drinkers. The qualitative survey assessed underlying reasons for these differences, in a subset of participants. Participants who associated water drinking with valued, rewarding outcomes were more likely to drink a high and consistent amount of water, with less subjective effort than participants who did not. Participants with health-conscious self-identities were more likely to associate water drinking with reward, but this association was disrupted in situations where other aspects of self-identity were prominent. Finally, for many participants drinking patterns from early life persisted into later life and were experienced as hard to change. Our results suggest that reward may be important in habit formation and maintenance. Interventions trying to increase water intake need to make water rewarding in line with drinking outcomes that people value. Early intervention is essential given the persistence of early life drinking habits.